Cooking Energy Conservation by Using Improved Stove: a Case Study on Thaipara Village of Magura Bangladesh - Biswas, GK; Hoque, MMM; Kabir, MH; Rehnuma, M (Journal of Environmental Science and Natural Resources, 2021)
The study was conducted to investigate the energy efficiency of traditional and improved cooking stove, potential energy conservation using improved stove and overall environmental impacts of those stoves at Thaipara of Magura district in Bangladesh. In the study area, almost 100% of the households use biomass as their cooking fuel in traditional stoves. Questionnaire Survey (QS) was conducted to fulfill the research objectives. The result of the study showed that total biomass energy consumption is 14897 GJ per year, whereas, the per capita cooking energy consumption is about 4.82 GJ per year. The results also revealed that biomass: fuel wood, dung and crop residues are the 100% sources of the total energy used in the cooking sectors. The combination of high demand aggravated by low use efficiency has contributed to deforestation, rural poverty and the energy shortage in the study village. Results of the study stated that by introducing improved stove with higher level of efficiency, well ventilation and using good quality of fuel can reduce the harmful impacts of cooking energy utilization and cooking systems on environment significantly. In this regard, formulation and implementation of a nationwide high efficiency cooking stove dissemination program would be very promising for cooking energy conservation at rural sectors. Environ. Sci. & Natural Resources, 12(1&2): 21-27, 2019